Photocatalytic behavior of Pt doped ZnO Nanoparticles in Methylene blue dye degradation - Irine T. M; S. Loice Bessylet; Abisha S Santham (The Bioscan, 2025)
Preparation of Platinum doped Zinc oxide nanoparticles was carried out using a combustion method at 500 °C. Zinc oxide nanoparticles were doped by different weight percent of platinum (1.0, 3.0, and 5. 0wt %). In this paper, with the aim of increasing its photocatalytic activity, zinc oxide (ZnO) was doped with Platinum (Pt). Characterization of the synthesized powders was done by X-ray diffraction (XRD), Thermogravimetric Analysis, FTIR, UV-Vis spectra, UV-Visible DRS. The prepared samples of photocatalytic performances were studied for degradation of methylene blue dye under UV irradiation. The XRD results showed successful doping of Pt in ZnO. XRD pattern of pt doped ZnO which is only composed the Zincite-type ZnO. It revealed that the size of Pt-doped particles was in the range of 63-82 nm. From TG curve shows 3.0 % sample revealed the best weight loss performance. Fourier transform infrared (FTIR) spectrum indicates the presence of Pt–ZnO stretching vibration at 418cm -1 UV-visible absorption peaks at 360 nm, its band gap decreased from 2.78 to 2.14 eV. The photocatalytic activity of platinum doped Zinc oxide nanoparticles was measured under UV irradiation for methylene blue dye degradation. The results showed that the 1% Pt-doped ZnO sample revealed the best performance. The resulting mixtures were irradiated with UV light for a period of 45 mins. The photocatalytic efficiency of 1% Pt- ZnO sample increased from 35% to 75%. Pt doped ZnO nanoparticles show better photocatalytic activity for the degradatiion of methylene blue compared to undoped ZnO nanoparticles.